Sociodemographic and clinical characteristics of patients with human immunodeficiency virus - Wesley Romário Dias Martins; Andréa Pereira da Silva; Fabiano de Araujo Silva; Jayra Adrianna da Silva Sousa; Joélio Pereira da Silva; Maria Luzinete Rodrigues da Silva (Universidade Federal do Ceará, 2019)
Objective: to describe the sociodemographic and clinical characteristics of patients diagnosed with the human immunodeficiency virus. Methods: this is a descriptive and documentary study, developed from the sociodemographic and clinical information registered in the identification sheets of 33 patients diagnosed with human immunodeficiency virus. Data were analyzed using the Statistical Package for the Social Sciences 18, with calculation of statistical measures and association between variables. Results: regarding the characteristics of the patients, the average age was 42 years, ranging from 20 to 64 years, 54.5% were women, married and with low level of education, 84.8% were heterosexual and exposed to the virus through of sexual intercourse (p=0.495). Conclusion: the patients with the infection were women, young, with low education and exposure to the virus due to sexual contact and unprotected sex with multiple partners.